Floristic study of the Bromeliaceae in Lençóis Maranhenses National Park, MA, Brazil - Elidio Armando Exposto Guarçoni; Milena Salazar-Ferreira (Hoehnea)
ABSTRACT (Taxonomic study of the Bromeliaceae in Lençóis Maranhenses National Park, MA, Brazil). The Lençóis Maranhenses National Park (PNLM) is located in the eastern region of the coast of the state of Maranhão, Northeastern Brazil, through the municipalities of Barreirinhas, Santo Amaro, and Primeira Cruz. It has an area of 155,000 hectares, with gently undulating relief and altitudes of less than 100 m. The vegetation is composed of a mosaic involving Mangrove, Cerrado and Restinga. Part of the Park is covered by a vast area of sand dunes, which form huge pools during the rainy season. Fieldwork was carried out in the municipalities of Barreirinhas and Santa Amaro. The testimonial material is deposited in the Maranhão Continental Herbarium (BMA). Four species in three genera were found: Aechmea (1 sp.), Ananas (1 sp.) and Bromelia (2 spp.). Identification key, descriptions, photographs, and ecological, taxonomic and geographic distribution comments are presented for each species located in the Park.